Changes in chemical attributes during ripening of traditional fermented sausage, "Pirot ironed". (September 2019) - Simunovic, S; Djordjevic, V; Bogdanovic, S; Dimkic, I; Stankovic, S; Novakovic, S; Tomasevic, I
Abstract: "Pirot ironed" is a traditional Serbian dry-fermented sausage manufactured in the south-east of Serbia. The changes in the chemical attributes of Pirot ironed sausage were followed during ripening. Samples were taken on the processing days 0, 7, 14, 21 and 28. Pirot ironed sausage was produced from the most valuable cuts of beef and chevon, without addition of starter cultures or fat tissues. Sausages were manufactured in a traditional drying/ripening chamber, where they were pressed every two days to acquire the typical flat form and to speed up the drying. The final water activity was 0.839. The lowest pH value recorded was 5.30 on the processing day 28. During ripening, the water content decreased significantly from 74.72% to 40.32%, while the protein and the fat amounts increased significantly from 19.12% to 45.79% and from 1.22% to 6.21%, respectively. Up to now, the properties of Pirot ironed sausage have not been recognized or published in scientific literature in spite of the long tradition and popularity of this meat product in Serbia.